On the semantics of German elements in the Turkish sentences: The mix language of Turkish teenagers in Mannheim [Zur semantik Deutscher elemente in Türkischen sätzen: Die mischsprache Türkischer jugendlicher in Mannheim] - (:unkn) unknown (My University, 2004)
This article examines the German-Turkish mixing practices used by young migrants of Turkish origin in Mannheim, Germany. It specially focuses on the semantics of the German elements in Turkish structures. The analysis, based on the categories "cultural borrowings" and "core borrowings", shows that only a small part of the German insertions fill lexical gaps in the Turkish lexicon where no equivalents exist A large part of the German insertions are ad-hoc borrowings. They derive from thematic areas that reflect situations from the everyday life of the young migrants in Germany. These kinds of insertions are used by speakers with a high competence in both languages.